2019
DOI: 10.3389/fimmu.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiation Therapy in Modulation of the Tumor Stroma and Microenvironment

Abstract: In recent decades, there has been substantial growth in our understanding of the immune system and its role in tumor growth and overall survival. A central finding has been the cross-talk between tumor cells and the surrounding environment or stroma. This tumor stroma, comprised of various cells, and extracellular matrix (ECM), has been shown to aid in suppressing host immune responses against tumor cells. Through immunosuppressive cytokine secretion, metabolic alterations, and other mechanisms, the tumor stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 133 publications
1
96
0
3
Order By: Relevance
“…Rich in cancer-associated fibroblasts, MDSCs, protumor growth M2 macrophages, and Tregs, 12 these components of the stroma function collectively to mediate treatment resistance and facilitate tumor progression. 13 We further hypothesize that low-dose radiation (L-XRT) directed to secondary tumors, delivered in combination with immunotherapy and H-XRT to primary tumors, can modify the stroma so as to enhance systemic antitumor benefits. We hereby showed that L-XRT treatment resulted in increased proportions of effector immune cells in the transplanted lung cancer murine tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Rich in cancer-associated fibroblasts, MDSCs, protumor growth M2 macrophages, and Tregs, 12 these components of the stroma function collectively to mediate treatment resistance and facilitate tumor progression. 13 We further hypothesize that low-dose radiation (L-XRT) directed to secondary tumors, delivered in combination with immunotherapy and H-XRT to primary tumors, can modify the stroma so as to enhance systemic antitumor benefits. We hereby showed that L-XRT treatment resulted in increased proportions of effector immune cells in the transplanted lung cancer murine tumors.…”
Section: Introductionmentioning
confidence: 99%
“…All these components that make up the TME components are known to be affected by IR and may therefore modulate therapeutic response [19,105]. In response to IR, the TME can promote immunogenic cell death through tumor antigen release [106] and induce vascular remodeling to improve radiotherapy efficiency [14], while conversely IR can also induce radioresistance through the promotion of EMT [107]. miRNAs are known to be involved in regulating the TME and radiotherapy response [108,109].…”
Section: Mirnas In Tumor Microenvironmentmentioning
confidence: 99%
“…Irradiated tumor cells would also undergo immunogenic cell death with the release of tumor antigens and various danger-associated molecular patterns (DAMPs) molecules [ 87 , 88 ]. This immunogenic cell death will further increase the process of immune recognition by antigen presenting cells, as discussed above.…”
Section: Hot Tumor Induction By Radiation Therapymentioning
confidence: 99%